Tenaga Kependidikan: Pengawas dan Kepala Sekolah - Marsena, Miftahul; Fatrisna, Yuli; Sesmira, Meli; Saputra, Septia Irnanda; Yuliani, Tri (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to find out the roles, functions, and problems of coaching supervisors and school principals. This research was conducted using a literature study method with a systematic approach. The data sources used are scientific articles, books, and research reports published in the 2014-2024 period. Literature searches are carried out through academic databases, namely Google Scholar using keywords relevant to the research topic. Data analysis is carried out by identifying the main themes and synthesizing findings from various sources to obtain comprehensive conclusions. The results of the analysis show that supervisors and school principals play a vital role in improving the quality of education. However, challenges in motivation, resource dispersal, and quality culture need to be overcome so that they can carry out their duties more effectively. Sustainable, need-based coaching from teachers and collaborative supervision are essential to achieve national education goals optimally.